Evaluation of interoperability in construction programs using the IFC 4 (2018)
BIM projects were defined as "value creating collaboration through the life cycle of an asset, underpinned by the creation, collation and exchange of shared 3-dimensional models and intelligent structured data attached to them" (Yousefzadeh, Spillane, Lamont, Mcfadden, & Lim, 2015). So, data exchange among construction programs is a very relevant aspect of construction projects. Since the introduction of different technology programs there has been a concern with the standardization of data exchange between construction programs. From 1997 the Industry Foundation Classes (IFC) was released, and it has enabled the exchange and sharing of information between building information models. The last version of IFC was the IFC 2x4 released in 2010, and it included several improvements to reduce the interoperability problem in construction projects. However, in this research the interoperability between different construction programs was evaluated using the IFC 4. The programs selected were Revit, Allplan, SAP 2000, EPANET and Plexos, and a four-story building was modelled. In the results the interoperability when transfering the model using the IFC 4 are mentioned. The conclusion of this paper is that although IFC data transfer could help to reduce time by transfering the construction models, there are still a lot of innacuracies to resolve. The academia, industry and software vendors should work together to mitigate the interoperability problem among BIM construction programs.